Faktor-faktor penentu tingkat pemahaman mahasiswa akuntansi - Ayu Chairina Laksmi; Raidho Satria Febrian (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2018)
Due to the current change and development of accounting in Indonesia, accounting students’ performance in terms of high Grade Point Average (GPA) alone is not enough. The students must also be able to show that they really understand accounting concepts. Thus far, higher education of accounting focuses more to theories which would be very different from the reality at work. As a consequence, the quality of accounting graduates is still far from what is being expected by the job market. This study aims to examine the effects of emotional intelligence, social intelligence, spiritual intelligence, learning behavior, secondary education background and college origin towards students’ level of understanding of accounting. A total of 100 respondents manually filled in questionnaires distributed in this study. The sampling method used was purposive sampling where only students from year 2013 were selected to be sampled. Data were analyzed by using multiple linier regression analysis. The results of the data analysis show that simultaneously, emotional intelligence, social intelligence, spiritual intelligence, learning behavior, middle school background and college origin, have a positive and significant effect on the students’ level of understanding of accounting with a significance value of 0.000 <0.05. The findings of this study can be used as feedback for universities to understand the factors that affect the level of understanding of accounting students and could aid in designing a learning system that aims to improve the level of understanding of accounting.